Associations of serum vitamin B6 status with the risks of cardiovascular, cancer, and all-cause mortality in the elderly - Wang, Pengxi; Huang, Jia; Xue, Feng; Abuduaini, Munire; Tao, Yuchang; Liu, Hongyan (Frontiers in Immunology, 2024)
Background There are few studies investigating the relationship between serum vitamin B6 and mortality risk in the elderly. This study hereby evaluated the associations between biomarkers of serum vitamin B6 status and cardiovascular, cancer, and all-cause mortality risks in the elderly. Methods Our study included a total of 4,881 participants aged 60 years or older from the National Health and Nutrition Examination Survey (NHANES) 2005-2010. Serum vitamin B6 status was estimated based on levels of pyridoxal 5’-phosphate (PLP), 4-pyridoxic acid (4-PA), and vitamin B6 turnover rate (4-PA/PLP) detected by high-performance liquid chromatography. Survival status and corresponding causes of death were matched through the National Death Index records through December 31, 2019. Multivariate Cox regression model was adopted to assess the relationships between serum vitamin B6 status and the risk of mortality. Results During a median follow-up period of 10.33 years, 507 cardiovascular deaths, 426 cancer deaths, and 1995 all-cause deaths were recorded, respectively. In the multivariate-adjusted Cox model, the hazard ratios (HRs) and 95% confidence intervals (CIs) for the highest versus the lowest quartiles of PLP, 4-PA, and 4-PA/PLP were 0.70(0.54-0.90), 1.33(0.88-2.02), and 2.01(1.41-2.79) for cardiovascular mortality, 0.73(0.52-1.02), 1.05(0.71-1.57), and 1.95(1.25-3.05) for cancer mortality, and 0.62(0.53-0.74), 1.05(0.82-1.34), and 2.29(1.87-2.79) for all-cause mortality, respectively. Conclusion Our study found that lower serum PLP levels were associated with increased risks of cardiovascular and all-cause mortality among the elderly population. And higher vitamin B6 turnover rate was associated with increased risks of cardiovascular, cancer, and all-cause mortality.